2020
DOI: 10.1186/s12917-020-02693-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fish skin as a biological dressing for metacarpal wounds in donkeys

Abstract: Background The use of biological dressings has recently emerged in the management of burns and wounds. The aim of the present study was to evaluate the Nile tilapia skin as a biological dressing for full-thickness cutaneous metacarpal wounds in donkeys. The study was conducted on nine clinically healthy donkeys (n = 9). Here, fish skin dressings were obtained from fresh Nile tilapia (Oreochromis niloticus and sterilized by immersion in silver nanoparticles (AgNPs) solution for 5 min, with no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
2
16
1
5
Order By: Relevance
“…Therefore, AgNPs have been commonly used as antimicrobial agent against drug resistant bacterial strains (Kvítek et al, 2008;Jones and Hoek, 2010;Lara et al, 2010;Ansari et al, 2011). AgNPs can also be applied in cases of burn, traumatic wound dressings, diabetic ulcers, coating of catheters, dental works, medical devices and water filtration (Jain and Pradeep, 2005;Silver et al, 2006;Gong et al, 2007;Kim et al, 2007;Thomas et al, 2007;Rai et al, 2009;Martinez-Gutierrez et al, 2010;Dosoky et al, 2015;Ibrahim et al, 2020). In the present study, the bactericidal effect of silver nanoparticles against MRSA and MSSA strains isolated from mastitic milk of small ruminants and their surrounding environment in Aswan was investigated.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, AgNPs have been commonly used as antimicrobial agent against drug resistant bacterial strains (Kvítek et al, 2008;Jones and Hoek, 2010;Lara et al, 2010;Ansari et al, 2011). AgNPs can also be applied in cases of burn, traumatic wound dressings, diabetic ulcers, coating of catheters, dental works, medical devices and water filtration (Jain and Pradeep, 2005;Silver et al, 2006;Gong et al, 2007;Kim et al, 2007;Thomas et al, 2007;Rai et al, 2009;Martinez-Gutierrez et al, 2010;Dosoky et al, 2015;Ibrahim et al, 2020). In the present study, the bactericidal effect of silver nanoparticles against MRSA and MSSA strains isolated from mastitic milk of small ruminants and their surrounding environment in Aswan was investigated.…”
Section: Introductionmentioning
confidence: 90%
“…Nesse trabalho o protocolo de preparação do curativo biológico seguiu etapas das metodologias citadas por outros autores como o processo de limpeza, recorte e esterilização (MIRANDA, 2018;IBRAHIM et al, 2020). Entretanto, baseando-se no trabalho descrito por Lima-Junior et al (2017), optou-se pela aplicação das etapas de preparo da pele, devido a praticidade, eficácia e por utilizar materiais de baixo custo.…”
Section: Resultsunclassified
“…Recentemente o enxerto de pele tem sido uma das técnicas reconstrutivas utilizadas por cirurgiões plásticos como alternativa biológica para auxiliar na cicatrização de feridas em pacientes humanos e em animais (SHIMIZU-HAYASHI e KISHI, 2012;IBRAHIM et al, 2020).…”
Section: Introductionunclassified
“…Application of equine amnion resulted in significantly less EGT J o u r n a l P r e -p r o o f formation than a non-occlusive dressing (Bigbie et al, 1991), although this was unconfirmed in other studies (Howard et al, 1993). A recent study investigating Nile tilapia skin on induced mid-metacarpal wounds of donkeys found the dressing resulted in no EGT formation, whereas control wounds treated with non-adherent pads showed signs of EGT (Ibrahim et al, 2020).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%